ERENCANAAN PERUBAHAN DALAM SUDUT PANDANG AL-QURAN: Analisa Al-Quran dalam Fundamental Perubahan Pendidikan - Zamakhsyari Abdul Majid (STIQ al-Lathifiyyah Palembang, 2019)
This paper is behind the concept of innovation that became one of the universal and fundamental strategy. The substance of innovation in education has the purpose of improving and updating the context of human development and educational institutions. Reference and inspiration of Islamic principles into modern theoretical problematic have a significant impact as the basic foundation of management science study in the future. Planning is part of a management science resulting from the process of human innovation of the object of education. This paper uses a method of commentary maudu'I or thematic interpretive analysis, which refers to a unity of certain themes in the verses of the Qur'an, as well as analyze the innovative part of planning in the perspective of Al-Quran. The study of educational innovation embodied in the Qur'an has implications for the human mindset to be able to plan the educational process systematically, objectively and dynamically. Planning human resources to the stage of management is a manifestation of human success to improve the paradigm of innovation that entered the world of education